Personalized SMS, Survey Participation and Data quality – The Italian Case. Issue 1 (October 2017) - Respi, Chiara; Sala, Emanuela
A number of papers have found that personalization of salutations in e-mail communications may lead to higher response rates. Given their widespread use, Short Text Messages (SMS) may also be useful contact modes in surveys. Using experimental data from an online survey on Italian graduates, this work intends to evaluate the impact of personalized SMS salutations on response and measurement error. We find evidence that personalization has a positive impact on response rates and some indication that it may lead to better survey data. Limitations and implications of the study are also discussed.